Coronaviruses – Potential human threat from foodborne transmission? (2020)
The COVID-19 pandemic has worldwide impact in terms of number of illnesses, deaths and long-term sequelae. While the main route for the spread of the SARS-CoV-2 virus is person to person from respiratory droplets, survival of the virus in the air and its ability to infect subsequently have raised concerns. COVID-19 outbreaks in meat and other food processing plants raise concern for potential of foodborne spread. We focus on the survivability of the virus in the food subjected to various unit operations during processing, storage and distribution and the risk to consumers. While the risk of contamination of food products is possibly due to survival of the virus in the air in food processing operations if preventive measures are not followed, survival of the virus on fresh foods is dependent on the intrinsic and extrinsic properties of the specific foods and antimicrobial interventions used during production. Even if the virus remains infective on contaminated foods, maintenance of infectivity after ingestion of food and subsequent invasion of tissue has not been reported. An alternate route of infection from contaminated foods can be during handling of foods and subsequent spread of the virus to other surfaces such as face, nose, leading to infection. However, due to the extensive treatments foods receive during processing, often inhospitable environs of the food products and further food preparation prior to consumption significantly reduce the risk of transmission of the SARS-CoV-2 virus.